Enhancing it project success through entrepreneurial leadership: the mediating roles of team reflexivity, team innovation culture, and team entrepreneurial passion - Diego Norena-Chavez; Rocio Romani Torres (Cogent Business & Management, 2024)
Drawing on the Resource Based View and Social Learning Theory, this study aims to explore the influence of Entrepreneurial Leadership (EL) on Project Success (PS) via the mediating pathways of Team Reflexivity (TR), Team Innovation Culture (TIC), and Team Entrepreneurial Passion (TEP). Data were gathered from 422 senior-level employees in IT firms. The analysis employed SMART-PLS 4 structural equation modeling to assess the proposed relationships. The findings underscore the significant impact of EL on PS. EL was observed to exert a noteworthy influence on TR, TIC, and TEP. Moreover, the proposed mediators, TR and TIC, exhibited substantial effects on PS, while TEP demonstrated a partially significant impact. Through the mediating roles of TR, TEP, and TIC, EL indirectly influenced PS.This research can help to understand how Entrepreneurial Leadership (EL) affects Project Success (PS) through Team Reflexivity (TR), Team Innovation Culture (TIC), and Team Entrepreneurial Passion (TEP). Results highlight EL's substantial impact on PS, TR, TIC, and TEP. The study fills a research gap, providing crucial insights for leadership and project success. It offers valuable implications for theory and practice in these domains
Keywords: M12; M14; 650; Entrepreneurial leadership; team reflexivity; project success; team innovation culture; team entrepreneurial passion